Investigation of learning style patterns: A case study of basic sciences medical students at Tabriz University of Medical Sciences - Gholamali Dehghani; Saeideh Ghaffarifar (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: A learning style refers to an individual's approach to perceiving, processing, and retaining novel information. Modifying instructional approaches to align with students' individual learning preferences enhances their learning. The current study was carried out to investigate the learning style preferences of students studying basic medical sciences at Tabriz University of Medical Sciences. Materials & Methods: This cross-sectional study was conducted from September 23, 2022, to February 10, 2023, on 230 students who were selected by the convenience sampling method. The data collection tool was a two-part questionnaire including demographic factors and the Kolb Learning Styles Scale (version 3.1). Data were analyzed through descriptive statistics, chi-square test, and one-way analysis of variance using SPSS-24. Results: The students had a mean age of 20.35 ± 1.85 years, with 53.9% men and 46.1% females. Dominant learning styles comprised 37.4% assimilating and 33.9% converging, comprising 71.3% of participants. Divergence and accommodation accounted for 21.7% and 7% of the remainder, respectively. No statistically significant difference was between dominant learning styles and demographic characteristics (p < 0.05). Conclusion: People with a preference for assimilating and converging learning styles show less interest in subjects that require communication with others. Therefore, it is necessary to improve students' interpersonal skills by using various educational strategies.